Dynamics of a Gross-Pitaevskii Equation with Phenomenological Damping - Renato Colucci; Gerardo R. Chacón; Andrés Vargas (International Journal of Differential Equations, 2013)
We study the dynamical behavior of solutions of an n-dimensional nonlinear Schrödinger equation with potential and linear derivative terms under the presence of phenomenological damping. This equation is a general version of the dissipative Gross-Pitaevskii equation including terms with first-order derivatives in the spatial coordinates which allow for rotational contributions. We obtain conditions for the existence of a global attractor and find bounds for its dimension.